2017
DOI: 10.1007/s41543-017-0002-9
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Life Satisfaction Scale: Analysis of Factorial Invariance Across Gender

Abstract: The purpose of the present study was to test the factor structure of the Students' Life Satisfaction Scale (SLSS) using confirmatory factor analysis, including tests of measurement invariance across gender. Data from a total of 921 middle school students (50.9% females, ages 11-15) were analyzed. Single group analyses showed that a modified one-factor model (with one residual covariance for the female group, and with two residual covariances for the male group) fit the data of each gender group adequately. Seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 40 publications
2
6
1
1
Order By: Relevance
“…A further look at the modification indices revealed that the fit could be significantly improved by allowing the error terms of two reverse‐coded items on the LS scale (items 3 and 4) to covary. This is consistent with Jiang and Huebner's () study suggesting the error covariance of these two items should be included to achieve a good model fit. Thus, we allowed the errors of the two LS items to be correlated, and this modified model showed an improved fit, χ 2 (163, N = 873) = 444.162; TLI, 0.942; CFI = 0.950; RMSEA (90% CI) = 0.044 (0.040–0.049).…”
Section: Resultssupporting
confidence: 91%
“…A further look at the modification indices revealed that the fit could be significantly improved by allowing the error terms of two reverse‐coded items on the LS scale (items 3 and 4) to covary. This is consistent with Jiang and Huebner's () study suggesting the error covariance of these two items should be included to achieve a good model fit. Thus, we allowed the errors of the two LS items to be correlated, and this modified model showed an improved fit, χ 2 (163, N = 873) = 444.162; TLI, 0.942; CFI = 0.950; RMSEA (90% CI) = 0.044 (0.040–0.049).…”
Section: Resultssupporting
confidence: 91%
“…The levels of life satisfaction (X = 3.82; SD = 0.83) reported in the current study are observed to be slightly lower than those reported using the same scale in other studies with similar samples ( Alfaro et al., 2017 ; Jiang and Huebner, 2017 ; Oyarzún et al., 2019 ). These differences may surely be due to the effect that the pandemic has had on the mental health and well-being of children and adolescents.…”
Section: Discussioncontrasting
confidence: 91%
“…Finally, as per the recommendation of Kline (2010), we deleted items with low factor loadings (<0.2). We sanctioned the removal of an item if it improved the CFI of the model by more than 0.01 (Jiang & Huebner, 2017). The initial model for the SLSS presented with an inadequate fit that improved substantially with the deletion of two items (Item 4: "I have what I want in life" and Item 5: "My life is better than most others my age") (see Model 2 in Table 4).…”
Section: Cfamentioning
confidence: 99%